Peran Vital Lembaga Pendidikan dalam Membangun Struktur Masyarakat yang Kokoh - Atika Nailah Syirva; Zaenab Niswati Kamali (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This article discusses the vital role of educational institutions in building a solid societal structure. Education serves as an agent of social change that not only transfers knowledge but also shapes the character and values ​​of individuals. Through education, individuals are taught to develop critical thinking, understand their rights and responsibilities, and actively participate in social and political life. This article also highlights how education can reduce poverty, promote gender equality, and strengthen democracy. Thus, educational institutions have a great responsibility in creating an inclusive, just, and sustainable society. Collective efforts from various parties are needed to overcome the existing challenges and ensure that education functions optimally in building a better societal structure.